2016
DOI: 10.1007/s00345-016-1884-5
|View full text |Cite
|
Sign up to set email alerts
|

Can we use baseline characteristics to assess which men with moderately symptomatic benign prostatic hyperplasia at risk of progression will benefit from treatment? A post hoc analysis of data from the 2-year CONDUCT study

Abstract: PurposeTo investigate (in a post hoc analysis of the 2-year CONDUCT study) the characteristics and clinical outcomes of men with moderately symptomatic benign prostatic hyperplasia (BPH) at risk of progression who benefitted from lifestyle changes alone.MethodsPatients were given lifestyle advice and randomized to a fixed-dose combination (FDC) of dutasteride and tamsulosin or watchful waiting (WW) and followed for 24 months. Patients in the WW group were escalated to tamsulosin if any follow-up International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…During these 6 years, the most active researchers were Roehrborn CG, Zorn KC, and Chughtai B. Roehrborn CG was major about PUL surgery and sexual function [ 29 ], focusing on aquablation surgery of the prostate [ 30 ], and using baseline characteristics to assess if the men could get benefit from potential treatments [ 31 ]. Zorn K.C.…”
Section: Discussionmentioning
confidence: 99%
“…During these 6 years, the most active researchers were Roehrborn CG, Zorn KC, and Chughtai B. Roehrborn CG was major about PUL surgery and sexual function [ 29 ], focusing on aquablation surgery of the prostate [ 30 ], and using baseline characteristics to assess if the men could get benefit from potential treatments [ 31 ]. Zorn K.C.…”
Section: Discussionmentioning
confidence: 99%
“…The answers are assigned points from 0 to 5. The total symptom score can, therefore, range from 0 to 35: mild (symptom score less than or equal to 7), moderate (symptom score range 8‐19) and severe (symptom score range 20‐35) 44‐46 …”
Section: Methodsmentioning
confidence: 99%
“…In the CONDUCT study, one third of the patients treated with watchful waiting (WW) plus lifestyle advices alone had an improvement of BPH symptoms as measured by improvement of IPSS score. A post-hoc analysis of the latter showed that WW plus lifestyle advices had similar efficacy to combination therapy of ARAs and 5ARIs in terms of IPSS score improvement, except for patients with heavy symptoms at baseline (Benign Prostatic Hyperplasia Impact Index [BII] 7–13) [ 39 ]. The lifestyle advices provided in this study were about caffeine and alcohol avoidance, bladder retraining, fluid management and avoidance of constipation [ 35 ].…”
Section: Con Sidementioning
confidence: 99%